Comparison of Learning Environment in 3 Different Settings to Support Clinical Skills Acquisition in Undergraduate Medical Students - Kirubashni Mohan; Ova Emilia; Widyandana Widyandana (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2012)
Background: Integration between preclinical basic science education, skills training program in the laboratory setting and real clinical setting is recommended. This study explores clinical setting which suitable for undergraduate skills training program. The purpose of this study is to compare 3 different clinical settings (Sardjito Hospital, Klaten Hospital, and Puskesmas), which is appropriate for undergraduate clinical skills training.Method: This was a descriptive quantitative study, using cross sectional method. Data collection used self administrated questionnaire comprised of clerkship students who pooled of Sardjito Hospital, Klaten Hospital and Puskesmas (Primary Health Centre). Data analysis was done using ANNOVA test.Results: The Puskesmas scored the highest mean compared to Sardjito Hospital and Klaten Hospital for an overall learning environment and also in the scales for autonomy, social support, and role clarity. Sardjito Hospital scored the highest mean for the scales of supervision, workload, emphasis on teaching and learning and variety. There is a positive correlation between the learning environment and skills practice opportunity.Conclusion: Puskesmas as primary health centers is a better overall clinical learning environment compared to Sardjito Hospital and Klaten Hospital, but scored low means in domains such as emphasis on teaching and learning and variety. There is a positive correlation between the learning environments and skills practice opportunity with different features for each setting. There is no correlation between skills practice opportunity and gender or marital status.